2006
DOI: 10.1177/1077558705283645
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Implementation in Physician Practices: A Qualitative Study of Practice Executive Perspectives on Pay for Performance

Abstract: Pay-for-performance (P4P) programs offer health care providers financial incentives to achieve predefined quality targets. Practice executives sit at a key nexus point for determining how P4P programs are implemented in physician practices. Using a qualitative interview design, this article examines the role practice executives play in the implementation of P4P programs and how their perspectives and decisions can influence the success of these programs. The authors identified five key findings related to prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 19 publications
0
55
0
2
Order By: Relevance
“…17 In general, sustainability of quality improvements may depend on changes in clinical systems that do not consistently add to the workload of busy clinical staff. However, sustainability may also vary depending on who receives the incentives.…”
Section: Discussionmentioning
confidence: 99%
“…17 In general, sustainability of quality improvements may depend on changes in clinical systems that do not consistently add to the workload of busy clinical staff. However, sustainability may also vary depending on who receives the incentives.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain active commitment rather than a grudging compliance, 4 previous research suggests it is important to align quality targets to professional priorities 9,22 and to ensure the underlying goals of quality targets are understood by those undertaking them. Our fi ndings, however, suggest that these issues are not necessarily relevant when targets are incentivized.…”
Section: Implications For Practice and Policymentioning
confidence: 99%
“…Despite this lack of enthusiasm, even those who criticized these new indicators were motivated to achieve the targets Previous research has suggested that fi nancial incentives are effective when they are deemed suffi cient to change the behavior necessary to meet the target and when they are used as bonus rewards in addition to existing income. 9 Professional motivation, while an important component of delivering quality improvement, is not always suffi cient on its own. 23 This nationally representative sample of doctors and nurses believed that the fi nancial incentives had been suffi cient to change behavior and to motivate achievement of QOF indicator targets.…”
Section: Pay F O R P Er F O R M a Nc Ementioning
confidence: 99%
See 1 more Smart Citation
“…e perspective of executives and directors, however, can provide an important strategic view of implementation. 42 Finally, we did not interview lower-performing physician organizations, so we are unable to contrast the care management and EHR capabilities Copyright 2014 The Joint Commission with the top-performing groups. Previous studies of "positive deviance" 43 in health care, however, underscore the usefulness of examining the experiences of top-performing organizations to identify facilitators of evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%